Designing and Explaining the Professional Development Model for Preschool Educational Managers in Education: A Mixed Method Study - Mohammadreza Maleki; Jafar Rahmani; Saeifullah Fazlullahi (Iranian Evolutionary Educational Psychology Journal, 2025)
Objective: This investigation was undertaken with the objective of formulating and elucidating a process model pertaining to the professional development of preschool educational administrators within the domain of education. Methods: This study uses a mixed-methods approach (qualitative-quantitative) to explore educational management. The qualitative phase involved in-depth, unstructured interviews with 11 experts (educational administrators, scholars, and HR consultants) using snowball sampling until theoretical saturation was reached. Grounded theory guided the model construction. The quantitative phase surveyed 217 preschool managers in Tehran and Qom provinces via a 42-item researcher-developed questionnaire, analyzed using SPSS and smart-PLS software. The study integrates qualitative insights with quantitative data to develop a comprehensive model, employing convenience sampling for the quantitative segment and grounded theory for qualitative analysis. Results: Ultimately, the findings of this research resulted in the formulation of a process model for the professional development of preschool educational administrators in education (anchored in the paradigm model structure), and the hypothesized relationships derived from the model were empirically tested and validated within a substantial population. Conclusions: The results may provide valuable insights for educational administrators and planners in the formulation and execution of a procedural framework aimed at the professional development of preschool educational managers.